Differentiation between glioblastoma and solitary brain metastases using perfusion and amide proton transfer weighted MRI - Knutsson, Malte; Salomonsson, Tim; Durmo, Faris; Johansson, Emelie Ryd; Seidemo, Anina; Lätt, Jimmy; Rydelius, Anna; Kinhult, Sara; Englund, Elisabet; Bengzon, Johan; van Zijl, Peter C. M.; Knutsson, Linda; et al. (Frontiers in Neuroscience, 2025)
ObjectivesEarly diagnostic separation between glioblastoma (GBM) and solitary metastases (MET) is important for patient management but remains challenging when based on imaging only. The objective of this study was to assess whether amide proton transfer weighted (APTw) MRI alone or combined with dynamic susceptibility contrast (DSC) MRI parameters, including cerebral blood volume (CBV), cerebral blood flow (CBF), and leakage parameter (K2) measurements, can differentiate GBM from MET.MethodsAPTw MRI and DSC-MRI were performed on 18 patients diagnosed with GBM (N = 10) or MET (N = 8). Quantitative parameter maps were calculated, and regions-of-interest (ROIs) were placed in whole tumor, contrast-enhanced tumor (ET), edema, necrosis and normal-appearing white matter (NAWM). The mean and max of the APTw signal, CBF, leakage-corrected CBV and K2 were obtained from each ROI. Except for K2, all were normalized to NAWM (nAPTwmean/max, nCBFmean/max, ncCBVmean/max,). Receiver Operating Characteristic (ROC) curves and area-under-the-curve (AUC) were assessed for different parameter combinations. Statistical analyses were performed using Mann–Whitney U test.ResultsWhen comparing GBM to MET, nAPTmax, nCBFmax, ncCBVmax and ncCBVmean were significantly increased (p < 0.05) in ET with AUC being 0.81, 0.83, 0.85, and 0.83, respectively. Combinations of nAPTwmax + ncCBVmax, nAPTwmean + ncCBVmean, nAPTwmax + nCBFmax, nAPTwmax + K2max and nAPTwmax + ncCBVmax + K2max in ET showed significant prediction in differentiating GBM and MET (AUC = 0.92, 0.82, 0.92, 0.85, and 0.92 respectively).ConclusionWhen assessed in Gd-enhanced tumor areas, nAPTw MRI signal intensity alone or combined with DSC-MRI parameters, was an excellent predictor for differentiating GBM and MET. However, the small cohort warrants future studies.